2020
DOI: 10.1039/d0md00227e
|View full text |Cite
|
Sign up to set email alerts
|

Recent developments in anticancer kinase inhibitors based on the pyrazolo[3,4-d]pyrimidine scaffold

Abstract: Pyrazolo[3,4-d]pyrimidines have become of significant interest for the medicinal chemistry community as a privileged scaffold for the development of kinase inhibitors to treat a range of diseases, including cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 137 publications
(185 reference statements)
1
38
0
1
Order By: Relevance
“…Acetylcholinesterase from Electrophorus electricus (C2888, Type V-S) was used in this study. In vitro effects on the AChE activity of the target N-alkylated pyrazolo [3,4-d]pyrimidine derivatives (4,10,12,14,16,18,20,22,24,26,28,30,32) were evaluated by the method of Ellman et al [55] TAC was used as the reference drug. All the measurements were repeated three times.…”
Section: Ache Activity Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…Acetylcholinesterase from Electrophorus electricus (C2888, Type V-S) was used in this study. In vitro effects on the AChE activity of the target N-alkylated pyrazolo [3,4-d]pyrimidine derivatives (4,10,12,14,16,18,20,22,24,26,28,30,32) were evaluated by the method of Ellman et al [55] TAC was used as the reference drug. All the measurements were repeated three times.…”
Section: Ache Activity Assaymentioning
confidence: 99%
“…Sapanisertib is an experimental kinase inhibitor, which is currently in clinical trials for several cancer indications. [12] Zaleplon and sildenafil are other FDA-approved drugs containing the pyrazolopyrimidine core structure. [13] The carbonic anhydrases (CAs) play a role in the reversible hydration of CO 2 into bicarbonate and protons.…”
mentioning
confidence: 99%
“… Structure-activity of some selected CDK-2 inhibitors [ 5 , 6 , 7 , 8 , 36 , 37 ] and structure design of our newly synthesized compounds 3 – 9 . …”
Section: Figures Schemes and Tablesmentioning
confidence: 99%
“…Therefore, there is a need to develop new anti-cancer agents [ 2 , 3 ]. Literature survey indicated that pyrimidine analogs are of considerable interest in drug discovery [ 4 , 5 , 6 , 7 , 8 ]. They possess remarkable biological activity especially as anti-cancer and anti-viral agents due to their resemblance to cellular pyrimidine bases involved in nucleic acids formation.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past years, some pyrrolo [2,3-d]pyrimidine derivatives were identified as inhibitors of Mer receptor and Src non-receptor tyrosine kinases, isoform of protein kinase B (Akt), mitotic checkpoint kinase (Mps1), Janus kinase 2 (JAK2), and phosphoinositide 3 kinase (PI3K) with promising anticancer activity [25][26][27][28][29][30][31][32][33]. Design strategy in development of purine derivatives as cytostatic agents for kinase inhibition revealed that introduction of cyclic amines improved the activity by forming an additional hydrogen bond to kinase hinge [9,34,35]. In addition, prevalence of halogenated drugs showed that halogen bonds contribute to the stability of protein-ligand complexes [36].…”
Section: Introductionmentioning
confidence: 99%